A Miracle Mirrored?: The Reception of Dutch Economic and Political Thought in Europe in the Seventeenth and Eighteenth Centuries - Ittersum, Martine Julia van (BMGN - Low Countries Historical Review, 2012)
This review article discusses recent publications by David Onnekink, Sophus Reinert, Gijs Rommelse, Jacob Soll, and Arthur Weststeijn from the perspective of the reception of Dutch economic and political thought in seventeenth- and eighteenth-century Europe. The Dutch Republic has been called ‘the first modern economy’ by Jan de Vries and Ad van der Woude. It looms large in ongoing academic and public policy debates about ‘The Great Divergence’, i.e. the question why the West made the transition to an industrialized economy around 1800, while China did not. Just how innovative the inhabitants of the Dutch Republic were in nearly all aspects of life is well-documented. Less attention has been paid to the reaction of contemporary Europeans. How did they perceive the Dutch example? What did they learn from it? Was the miracle really mirrored elsewhere? These are questions that deserve more attention than they have received in Dutch historiography hitherto.